Why do home owners work longer hours? - Renata Bottazzi; Hamish Low; Matthew Wakefield (Institute for Fiscal Studies (IFS), 2007)
This paper uses a structural model to address the question of why home-owners with large mortgage debt work longer hours than those without such debt. We consider whether this is due to lower net wealth or to capital market imperfections, including mortgage constraints that depend on current earnings and, therefore, labour supply choices. We show that the need to meet current mortgage commitments can generate the observed correlation, and this impact of current commitments arises from the institutional borrowing constraints. We also show that labour supply as a function of household debt is highly nonlinear: those with greater debt are more likely to face binding borrowing constraints and their labour supply is more variable. – Housing ; labour supply ; life-cycle models ; borrowing constraints
Keywords: J22; D91; 330; Grundbesitz; Arbeitsangebot; Arbeitszeit; Private Verschuldung; Lebenszyklus; Großbritannien